Edukasi PHBS Pada Ibu Rumah Tangga Di Desa Baet Meusagoe Kecamatan Sibreh Kabupaten Aceh Besar - Kiki Rezeki Amelia; Fadli Syahputra (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2023)
Clean and Healthy Living Behavior is a set of behaviors that are carried out based on awareness as a result of learning that enables a person or family to help themselves in the health sector and play an active role in realizing personal and family health. the implementation of PHBS in households is the responsibility of every household member. According to Basic Health Research (Riskesdas) in 2013, the proportion of households that met PHBS criteria was 32.3%. The purpose of this education is to increase the knowledge of housewives about problems with PHBS. The methods used in this counseling are pre-test and post-test using questionnaires and question and answer lectures. The results of the pre test for housewives who were present at the extension activities were in the low category (18%) and after being given knowledge counseling the respondents were in the high category (81%). The conclusion regarding this counseling is that there is a very significant increase in knowledge of the respondents before being given education with after being given counseling about PHBS.